STUDI TENTANG KONSEPSI (MAHA)SISWA DALAM MEMAHAMI FENOMENA PERGANTIAN SIANG DAN MALAM - Theo Jhoni Hartanto; Susi Marcelina (Vidya Karya, 2019)
Abstract. Everyone must experience regular day and night changes. The question is: how could the day and night shift occur? It is often not all people's understanding of the event is in accordance with scientific concepts. This article describes the conceptions of a number of students about the day and night turnover events. This study was carried out through pictures and explanations from each participant's interview. Participants in this study consisted of 10 high school students and 16 first year students of Physics Education Study Program, all participants lived in Palangka Raya and its surroundings. Based on the results of the study, students still have many misconceptions about day-night shifts, for example the conception of revolving Earth models, rotation models, revolving sun-moon models, and blocking models. The conceptions found in this study have similarities with the results of studies abroad in various age groups and levels of education. Keywords: day and night, conception, scientific concept Abstrak. Setiap orang pasti mengalami pergantian siang dan malam secara beraturan. Pertanyaannya: bagaimana peristiwa pergantian siang dan malam itu bisa terjadi? Seringkali tidak semua pemahaman orang-orang terhadap peristiwa tersebut sesuai dengan konsep ilmiah. Artikel ini mendeskripsikan konsepsi dari beberapa siswa dan mahasiswa tentang peristiwa pergantian siang dan malam. Studi ini dilaksanakan melalui gambar dan penjelasan dari wawancara masing-masing partisipan. Partisipan dalam studi ini terdiri dari: 10 siswa sekolah menengah dan 16 mahasiswa tahun pertama Prodi Pendidikan Fisika, seluruh partisipan tinggal di Kota Palangka Raya dan sekitarnya. Berdasarkan hasil studi, pada siswa dan mahasiswa masih banyak konsepsi-konsepsi yang salah tentang pergantian siang-malam, misalnya konsepsi revolving Earth model, rotation model, revolving sun-moon model, dan blocking model. Konsepsi-konsepsi yang ditemukan dalam studi ini memiliki kemiripan dengan hasil-hasil studi di luar negeri pada berbagai kelompok umur dan jenjang pendidikan. Kata kunci: siang dan malam, konsepsi, konsep ilmiah